(untitled) (Eurasian Journal of Philology Science and Education, 2016)
At any period of history, you can appreciate the role of functions of language in social development, as the level of development of the national culture is closely linked with the development of language. One of the lexical categories enriching the literary language and culture, as well as its artistry and imagery, is phraseology. Our paper considers phraseological units with color components. The concept of colour is generated due to certain circumstances, and it shows the cultural life, traditions, geographical habitat, religion, beliefs, philosophy, and psychology of each nation. In this article, it is shown how phraseological units with colour components in the Kazakh and English languages may become indicators of ethnocultural differences. The given examples illustrate phraseological units with often/rarely used colour components in both languages. It is well known, that in every language, phraseological units with colour components can reflect customs, world outlook, mode or way of life.